2007
DOI: 10.1097/wnp.0b013e31815068d5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Event-Related Evoked Potentials N200 and P300 Subcomponents in Early Diagnosis of Alzheimer’s Disease and Mild Cognitive Impairment

Abstract: Event-related potentials (ERPs) have a large application in the evaluation of cognitive processes, particularly in Alzheimer's disease (AD). The aim of the present study was to evaluate the clinical relevance of event-related evoked potentials (N2 and P3 subcomponents) in early diagnosis of AD and mild cognitive impairment (MCI). We prospectively studied 60 subjects. They all underwent the following investigations: neurologic and neuropsychological examination; functional evaluation, i.e., ERPs; cerebral image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
119
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(131 citation statements)
references
References 30 publications
11
119
0
1
Order By: Relevance
“…Importantly, the improved cardiorespiratory fitness was associated with improved executive function for aMCI women [48]. These substantial findings suggest that although elderly people with aMCI had declines in executive control processes as a function of neuropathological aging [20,29,[33][34][35], they still exhibited cognitive and neural plasticity and their task-switching deficits appear amendable to an intervention based on increased physical activity.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Importantly, the improved cardiorespiratory fitness was associated with improved executive function for aMCI women [48]. These substantial findings suggest that although elderly people with aMCI had declines in executive control processes as a function of neuropathological aging [20,29,[33][34][35], they still exhibited cognitive and neural plasticity and their task-switching deficits appear amendable to an intervention based on increased physical activity.…”
Section: Discussionmentioning
confidence: 74%
“…Several reports over the past decade described the potential diagnostic importance of electrophysiological markers of cognitive decline in patients with MCI and the preclinical stage of AD, as obtained by analysis of the electroencephalography-derived event-related potentials (ERPs) [20][21][22][23][24][25][26][27][28][29]. For example, the ERP P2, N2, and P3 components are recognized as effective electrophysiological indices in the early stage of MCI diagnosis [20][21][22][23], as MCI subjects have prolonged P2, N2, and P3 latencies, and reduced P3 amplitudes, compared to healthy elderly controls [20,[24][25][26]. Even specific to the MCI subgroups [e.g., amnestic MCI (aMCI)], these ERP components may also be useful for observing the differences in cognitive processes from those of the healthy elderly [20,24,27,28], and to distinguish the different MCI subtypes (e.g., aMCI versus nonaMCI) [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the major waves observed in the ERPs (N200, P300 and Slow Wave), P300 component corresponds to mental processes such as recognition, categorization of stimuli, expectancy or short-term memory while there are many regions in the brain, especially in the temporal lobe, the parietal lobe and the hippocampus which are thought to be responsible for its generation (Bennys et al,2007). …”
Section: Discussionmentioning
confidence: 99%
“…P300 testing has been demonstrated to be a method of choice in differential diagnostic assessment of neurological and psychiatric diseases (Table 1). Clinical research showed significant changes in P300 parameters, such as lowered amplitude and extended latency, in patients with dementia, Alzheimer's disease, and mild cognitive impairment [MCI] (11)(12)(13)(14)(15)(16)(17)(18)(19). A smaller number of studies indicated changes in P300 in patients with epilepsy, and in those taking antiepileptic drugs (10,20).…”
Section: Review Of Literaturementioning
confidence: 99%